Acute Segmental Testicular Infarction caused by COVID-19 Disease: A Case Report and Current Literature Review - Murat Demir; Ilyas Dundar (Haseki Tıp Bülteni)

(untitled)
Coronavirus disease-2019 (COVID-19) is known to cause sepsis-associated hypercoagulopathy. Thromboembolic complications affecting many systems associated with COVID-19 disease have been described in the literature. The direct effect of this virus on male urogenital organs and possible testicular damage is still being evaluated. Follow-up studies in recovering male patients are necessary to investigate the possibility of testicular damage. In this article, we aimed to present a 30-year-old patient who presented with acute testicular pain and was diagnosed with testicular infarction due to COVID-19 with ultrasonography and contrast-enhanced magnetic resonance imaging findings.